Encrypted mobile messaging application using 3D-AES block cipher cryptography algorithm / Aida Najihah Mohd Khlubi - Mohd Khlubi, Aida Najihah (2019)
This paper analyzes how information sent through mobile messaging application is being secured. Nowadays, people are more likely to communicate with each other through mobile application. There is a high possibility that the information could have been leaked to intruders. It is crucial to maintain the confidentiality and privacy of the information. Therefore, securing the information sent via mobile messaging application is important by implying the cryptography technique. Cryptography technique comprises encrypting and decrypting information which can only be seen by the sender and receiver. This paper focusing on encrypting and decrypting text sent through the application. The process of securing the text is by using the 3Dimensional-Advanced Encryption Standard (3D-AES) block cipher algorithm. Android Studio software is used in developing the project. The data involved is stored in database by using Firebase database. The text will be encrypted first before sending it to the intended receiver. A specific key is used to encrypt and decrypt the text, which can only be known and accessed between the sender and receiver. The result of this project is based on the efficiency of securing the messages through encrypting and decrypting them. This project provides protection to any personal conversations between the sender and the receiver and it secure the people’s personal information by applying the encryption and decryption method.